Verification, validation and evaluation for quality of services of expert system for bus - Norhisham S.; Khalid N.H.N.; Isa N.A.M.; Ismail A.; Borhan M.N. (International Research Publication House, 2023)
In developing expert system for quality of services, there is five step methodology namely Task Analysis, Knowledge Acquisition, Prototyped Development, Expansion & Refinement And Finally Verification, Validation And Evaluation. In this paper is highlight of case study verification, validation and evaluation proses of the expert system. In this case study an expert system for quality of services for bus. In Verification proses, and couple of error had identified. It is a process to make sure the programming is complete. The verification proses done successfully. Validation process is a comparison with normal results calculation and checking with comparison with expert system output. Validation process had been validate same as normal calculation process. Same as Evaluation process, 5 evaluators had been assign to use the system and give and input of their experience using the system. Results showed BUS-QOS verification has yielded satisfactory results where the manual calculation and BUS-QOS is almost 100% match. Based through the results, it shows the advantages of using bus-QOS which is faster and encouraging in assessing level of service. International Research Publication House.